The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1021/ol401729m
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Decarboxylative Alkenylation of Enolates

Abstract: A palladium-catalyzed decarboxylative alkenylation of stabilized enolates has been developed, which gives rise to alkenylated dicarbonyl products from enol carbonates regioselectively with concomitant installation of a quaternary all-carbon center. The broad scope of the reaction has been demonstrated by successfully utilizing a range of enolates and external phenol nucleophiles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 36 publications
2
33
0
Order By: Relevance
“…The resulting solid was dissolved in EtOAc and purified by column chromatography (hexane/EtOAc, 1:2) to afford 12 (3.6 g, 83 %) as a white solid. The spectroscopic data of 12 were identical to those of the previous report …”
Section: Methodssupporting
confidence: 82%
See 1 more Smart Citation
“…The resulting solid was dissolved in EtOAc and purified by column chromatography (hexane/EtOAc, 1:2) to afford 12 (3.6 g, 83 %) as a white solid. The spectroscopic data of 12 were identical to those of the previous report …”
Section: Methodssupporting
confidence: 82%
“…Our synthetic study started by preparing diketone 10 from dimedone ( 11 ) as shown in Scheme . Mono‐methylation to the activated methylene moiety of dimedone ( 11 ) by using a modified procedure reported by Franckevicius gave compound 12 in 83 % yield. Although the direct introduction of the butenyl group to compound 12 was attempted under several conditions, desired diketone 10 was obtained in low yield.…”
Section: Resultsmentioning
confidence: 99%
“…We reasoned that, if the  3 - This strategy proved to be successful in the coupling of propargyl enol carbonates 132 with phenols 74 to give 135, which contains an all-carbon quaternary center (Scheme 30). 41 A variety of cyclic and acyclic 1,3-dicarbonyls, as well as phenols decorated with electron-donating, -withdrawing and nucleophilic groups can be readily used, affording products 135a-g in high yields with complete chemo-and regioselectivity. Mechanistic studies indicated that the palladium center was indeed tightly associated with the enolate after decarboxylation, resulting in complete control of selectivity.…”
Section: Control Of Selectivity: Intermolecular Coupling Reactions Ofmentioning
confidence: 99%
“…Indeed, we have found this to be the case in the coupling of 1,3-dicarbonyls with phenols to generate structures of type 12. 13 Subsequently, we reported the coupling of two different 1,3-dicarbonyl compounds (13), 14 the regioselectivity of which can be controlled by judiciously adding one of the nucleophiles as the propargyl enol carbonate. In the first instance, we tested the reactivity of propargylic carbonate 15a derived from a 1,3diketone and indole (16a) in the presence of a source of palladium(0) and a phosphine ligand in 1,4dioxane as the solvent at 80 °C (Table 1).…”
mentioning
confidence: 99%
“…H and13 C NMR spectra for all novel compounds.Mass and 1 H NMR spectra of compounds arising from deuterium-labeling experiments.Crystallographic data for 17d and 23b (CIF).…”
mentioning
confidence: 99%